Growth and Production Performance of Sugar Cane (Saccharum officinarum L.) Clon SB 01, SB 04, sb 19, SB 20 in the Village Curahmalang, Jombang Regency - Setyo Budi; Wiharyanti Nur Lailiyah (OJS Universitas Muhammadiyah Gresik, 2023)
Sugar productivity decreased in 2015-2016 by 11.76% and reached the lowest productivity in 2017 of 4,985 kg/ha White Crystal Sugar (GKP). The reason could be due to the presence of several types of sugarcane that experienced a decrease in yield during cultivation, such as nutrient deficiencies which resulted in divergent sugarcane plant height. Then the low sugarcane juice contained in sugarcane plants also affected production results. This study aimed to determine the growth and yield performance of sugarcane (Saccharum officinarum L.) clones SB01, SB04, SB19, SB20. This research was conducted in the garden of the Center for Sugarcane Research and Development (P3T) Faculty of Agriculture, University of Muhammadiyah Gresik, PG GEMPOLKREP and PT Perkebunan Nusantara X (PTPN X). Sumobito District, Jombang Regency from March to June 2021. Materials for observations used clones SB 01, clones SB 04, clones SB 19, and clones SB 20. The variables observed were sugarcane shoots, sugar cane stalks, and sugarcane leaves. Data analysis used descriptive analytical, variability and heritability.